Candidate Biomarkers to Evaluate the Association Between Psychosocial Stressors and Cardiovascular Diseases. A Short Review - Ayari, Hanène; Zeller, Marianne (European Journal of Mental Health, 2023)
Introduction: The association between psychosocial stressors and cardiovascular diseases had been suggested. Aims: This review was performed to assess, from literature data, the pertinence of using new biomarkers in the occurrence or prognosis of cardiovascular diseases in a psychosocial context. Methods: We choose to consider wide-ranging descriptions of psychological stressors (occupational stress, financial strain, marital stress, social isolation, etc.) that may induce or influence the cardiovascular diseases’ outcome. We addressed literature data confirming the link between candidate biomarkers, such as cortisol, endothelial dysfunction, pro-inflammatory cytokines, allostatic load, and cardiovascular diseases. Results and Conclusion: Herein we showed a link between cortisol, endothelial dysfunction, pro-inflammatory cytokines, and the incidence or prognosis of cardiovascular diseases in a psychosocial context of stress. Allostatic load index was also identified as a pertinent tool in the assessment of the cumulative psychosocial stressors’ burden exerted on the body.